IMPLEMENTASI PENGGUNAAN MEDIA INTERAKTIF UNTUK MENINGKATKAN KETERAMPILAN MENULIS PADA MATA PELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR: KAJIAN LITERATUR - Ar, Zulkarnain; Haryadi, Haryadi; Santoso, Bernadus Wahyudi Joko (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the effectiveness of interactive media in improving elementary school students’ writing skills in Indonesian language learning. Using a Systematic Literature Review (SLR) approach, this research analyzed ten national and international studies published between 2021 and 2025. The findings reveal that various types of interactive media—such as Padlet, digital storytelling, animated videos, EPUB-based platforms, and artificial intelligence (AI) applications—significantly enhance students’ writing abilities in terms of structure, vocabulary, coherence, and creativity. Moreover, interactive media foster learning motivation, collaboration, and digital literacy among students. The use of interactive digital tools aligns with constructivist learning theories that emphasize active and reflective learning experiences. However, the success of implementation depends on teacher readiness, technological infrastructure, and institutional support. Theoretically, this study enriches the literature on digital-based innovations in Indonesian language learning. Practically, the results serve as a reference for educators and curriculum developers in designing creative, participatory, and contextually relevant writing instruction aligned with 21st-century literacy competencies.